2001
DOI: 10.1021/jm000502n
|View full text |Cite
|
Sign up to set email alerts
|

QSAR Study on the Contribution of Log P and Es to the in Vitro Antiprotozoal Activity of Glutathione Derivatives

Abstract: A series of N-S-blocked glutathione monoester and diester derivatives based on N-benzyloxycarbonyl-S-(2,4-dinitrophenyl)glutathione were evaluated for activity against the pathogenic parasites Trypanosoma brucei brucei, Trypanosoma cruzi, and Leishmania donovani in vitro.Only monoesters 7-9 with a log P value of >2.7 were active inhibitors of T.b. brucei bloodstream form trypomastigotes. Diester compounds 10-15 and 17-27 in most cases were better inhibitors of T.b. brucei than monoester compounds, and some dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 18 publications
3
31
1
Order By: Relevance
“…In that study a model was proposed in which these compounds inserted into the membrane of T. b. brucei cells via weak lipophilic forces, compromising structural and membrane fluidity. 26 The studies reported here further support that view, with the N-substituents of glutathione contributing to a small increase in lipophilic binding energy of 1.2-5. ).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In that study a model was proposed in which these compounds inserted into the membrane of T. b. brucei cells via weak lipophilic forces, compromising structural and membrane fluidity. 26 The studies reported here further support that view, with the N-substituents of glutathione contributing to a small increase in lipophilic binding energy of 1.2-5. ).…”
Section: Discussionsupporting
confidence: 79%
“…As previously observed glutathione compounds with a log P of 4.0-7.0 showed the highest in vitro activity against Trypanosoma. 26,27 Compound 8 containing the N-myristoyl group(log P: 8.73) proved no exception and showed significantly reduced activity versus 2. Compound 20, although similar to the substrates of the P2 receptor showed no enhanced activity in the inhibition of trypanosome growth.…”
Section: Screening Against T B Rhodesiense L Donovani and Tcruzimentioning
confidence: 99%
See 2 more Smart Citations
“…33 The chemical structure of 10 and 11 is presented in Figure 3. These results presented above together with the biological activity of glutathione derivatives reported by D'Silva et al 34,35 targeting trypanothione metabolism encouraged us to prepare analogues assuming that the optimum glutathione tripeptide derivative should be L-γ-Glu-L-LeuGly. Compound 12, a protected tripeptide derivative of glutathione, was moderately potent against T. brucei (ED 50 = 1.9 µM) but exhibited vanishing biological activity against T. cruzi ( Figure 4).…”
Section: Introductionmentioning
confidence: 87%